Opportunities for plain packaging of tobacco products in the Philippines: results of a nationwide online survey - Arda, John Rafael Y.; Amul, Gianna Gayle H.; Mallari, Eunice U.; Santiago, Alen Josef A. (Frontiers in Public Health, 2024)
Objective This study aimed to contribute to local research evidence to promote the implementation of plain packaging of tobacco products in the Philippines. The study aimed to assess Filipinos’ perception of the effectiveness of plain packaging and their readiness by assessing the potential impact of plain packaging. Methods We conducted a nationwide geographically representative online panel survey with a sample size of 2,000 Filipinos. The survey recruited respondents 18–65 years old and residing in the Philippines, with 500 respondents each from the National Capital Region, Luzon, Visayas, and Mindanao. We showed respondents six different mock-ups of cigarette packs in plain packaging, with two sizes of graphic health warnings (50 and 75%) and three plain packaging colors (black, white, and Pantone 448C). Using five-point Likert scales, participants rated their agreement with 18 items assessing readiness and rationales for plain packaging and 54 items related to pack design (9 items for 6 pack designs). Results The study showed that Filipinos recognize the value of adopting plain packaging with larger graphic health warning labels on tobacco products in the Philippines. Both non-smokers and smokers agreed that plain packaging has the potential to reduce the attractiveness and appeal of packs, prevent advertisement and promotion of tobacco products, reduce the ability of tobacco products to mislead consumers, increase the noticeability and effectiveness of the pictorial health warnings, increase recall of the pictorial health warnings, affect consumer perceptions of the attractiveness of the tobacco products and their relative safety, reduce youth experimentation with the use of tobacco products, prevent the use of tobacco brand variants as a promotional tool, prevent branding targeted toward youth, promote quitting among current users, and to more clearly inform consumers about the harmful effects of tobacco use. Conclusion We recommend that policymakers pursue plain packaging as legislation or as part of a reform of the Philippines’ graphic health warnings law. The law should target tobacco products sold in the Philippines.